2021
DOI: 10.3390/polym13152418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bond Integrity, Durability, and Degree of Conversion of a Calcium Fluoride Reinforced Dentin Adhesive

Abstract: Our study aimed to synthesize and compare the mechanical properties and dentin interaction of two adhesives; experimental adhesive (EA) and EA containing 5 wt.% calcium fluoride (CaF2) nano-crystals (CaF2 adhesive-CAFA). CaF2 nano-crystals were synthesized by reacting two solutions (containing calcium and fluoride) in a glass chamber using a heated air system. The EA was produced using a mix of monomers, photo-initiators, camphorquinone, and electron initiators. The synthesized CaF2 nano-crystals were centrifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The study clearly showed that addition of BNNS fillers has increased the DoC significantly, which is highly desirable for any adhesive system. Polymers 2023, 15, x FOR PEER REVIEW 6 of 14 fluoride-nanofiller-added sample had a higher DoC (61.54 ± 4.07) in comparison to the control (56.8 ± 5.5) [51]. The study clearly showed that addition of BNNS fillers has increased the DoC significantly, which is highly desirable for any adhesive system.…”
Section: Degree Of Conversionmentioning
confidence: 77%
See 1 more Smart Citation
“…The study clearly showed that addition of BNNS fillers has increased the DoC significantly, which is highly desirable for any adhesive system. Polymers 2023, 15, x FOR PEER REVIEW 6 of 14 fluoride-nanofiller-added sample had a higher DoC (61.54 ± 4.07) in comparison to the control (56.8 ± 5.5) [51]. The study clearly showed that addition of BNNS fillers has increased the DoC significantly, which is highly desirable for any adhesive system.…”
Section: Degree Of Conversionmentioning
confidence: 77%
“…In a similar study, Degrazia et al (2017) showed that with an increase in the addition of boron nitride nanotubes, the DoC increased until 0.1% (87.97 ± 1.65% for control and 91.74 ± 0.43% for 0.1% sample), but the addition of 0.15% of the nanotubes decreased the DoC (89.54 ± 1.29%) [1]. Similarly, in another study, AlRefeai et al (2021) showed that the calcium-fluoride-nanofiller-added sample had a higher DoC (61.54 ± 4.07) in comparison to the control (56.8 ± 5.5) [51]. The study clearly showed that addition of BNNS fillers has increased the DoC significantly, which is highly desirable for any adhesive system.…”
Section: Degree Of Conversionmentioning
confidence: 81%
“…Various compositional analysis methods are available on the market. In this study, SEM with a built-in EDS was used due to the simplicity and reliability of this combination as a multimethod for detecting, assessing, and compositional analysis, either to suspected contamination on implants as in the current study or to other devices and materials used in the dental field [ 19 , 36 , 38 ]. The EDX analysis revealed that almost every implant has carbon residuals on the surface, findings that agree with most studies [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…EDX is a standard method frequently used in dental research to analyze the elemental compositions in organic and inorganic material samples [ 5 , 14 , 25 , 30 , 36 , 37 , 38 , 39 ]. An electron beam projects toward the sample‘s surface, excites it, and causes the emission of variable X-ray photons; an energy-dispersive X-ray spectroscopy detector (EDS) identifies the distinctive energy of each element [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of literature have shown that F and Ca have a strong affinity. Supplementary Ca forms a novel complex, insoluble CaF 2 , in the intestine by combining with F, which reduces the absorption and toxicity of fluoride ( 51 ). However, a large amount of serum calcium into bone tissue will lead to increasing bone mineral density, hyperosteogeny, hypocalcemia.…”
Section: Potential Molecular Mechanism Of Mitochondrial Dysfunction I...mentioning
confidence: 99%